Pete the Kitty and the unicorn's missing colors - Dean, Kim, 1969-; Dean, James, 1957- (Pete the kitty., 2020)
Pete the Kitty's friend Stevie the unicorn somehow lost all the colors in her rainbow tail. It's a good thing Pete has his magical paintbrush to help out! Together, they search for the missing colors of the rainbow.